Beyond greed and grievance: understanding the multi-causal factors of the Niger Delta conflicts - Akintola, O (2018)
This thesis attempts to highlight some of the factors driving the Niger Delta conflicts. First, by exploring the limitations of economic understanding of conflicts and reviewing the policy implications of assessing these unrests through a singular economic lens, my research sought to underline the need to shift beyond singular issue understanding of the region’s unrests. To drive this shift in the assessment of conflicts, I adopted a multifocal, interdisciplinary approach to complement the economic school and its assessment of conflictual issues in the region. This was achieved by assessing the micro dynamics of disputes in four communities in the Niger Delta. Structured as three case studies, emphasis was placed on examining the nuances that undergirded some of the frequent clashes in the region. In assessing these randomly selected communities, I was attempting to explore in detail, the factors that continue to drive conflicts in the Niger Delta. Through this examination, it was possible to focus on some factors that had previously received very little attention in the study of the region. In a case study exploring militancy, charting Ateke Tom’s rise, I was able to show that militant leaders were dextrous actors who leveraged federal government’s dependency on the region’s oil to secure privileges for themselves and for the people of the Niger Delta. Though commonly understood as ‘criminals masquerading as freedom fighters’ I was able to show that ex-militant leaders are important actors in a new system of alternative governance in the Niger Delta. This system involves ex-militant leaders providing goods and services in lieu of state provisions. This allows these actors to manage tensions in the region - in return for these provisions, they maintain access to state’s decision making and the privileges attached to accessing key stakeholders. In another section of the thesis, I explored communal conflicts in the region and identified that government’s interest in the region’s peace is directly correlated with presence of natural resources. Communities with no natural resources were more likely to be ignored by state institutions. Instead of relying on state intervention, communities involved in conflicts appear to depend heavily on the existence of ‘sons of the soil’. These actors, in my case studies, were patrons who treated their communities as ‘communal clients’ who had to be protected from external threats. Often using state resources, patrons who were ‘sons of the soil’ leveraged their government positions to disenfranchise rival communities. Instead of assuaging competing factions, the process of using federal government resources to protect communal clients was found to exacerbate tensions in the region. The thesis was also able to highlight the frictions emanating from internal governance struggles. By focusing on a community with ongoing chieftaincy disputes, I was able to explore the source of the tensions between chiefs in the community. Interestingly, the chieftaincy dispute had a generational dimension where youths were pitted against each other, but also against traditional elites. After many interviews, and discussions with opposing camps and interest groups, I was able to challenge the idea of generational crisis where modernity is assumed to be in direct competition with tradition. I conclude by positing that there is in fact a transgenerational continuum whereby the interests of youths, the agents of modernity, and traditional elites, the custodian of tradition, are much more aligned than was previously thought. Overall, the thesis was able to draw attention to some of the multiple causes of the Niger Delta conflicts. It was important to note that the factors driving conflicts in the region are many and are varied, but it was also important to emphasise that the conflicts in the Niger Delta were neither unique nor exceptional. I conclude by challenging the idea of Niger Delta exceptionalisam. I argue that, although the region unlike many other regions in Nigeria has been able to leverage its resources to gain attention domestically and internationally, the underlying factors driving conflicts in Niger Delta can be found across Nigeria.